1993
DOI: 10.1046/j.1523-1739.1993.07030719.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and Conservation Biology of Cichlid Fishes as Revealed by Faunal Remnants in Northern Lake Victoria

Abstract: Lake Victoria until recently harbored the world’s second richest lacustrine fish assemblage, but it is now experiencing a mass extinction. Here we report on the current status of the endemic cichlid fishes from a preliminary biotic inventory conducted as part of limnological reconnaissance in Kenyan and Ugandan waters during 1989–1992. Sixty‐two haplochromine taxa were recovered, half of them new. Some are local endemics, while others are more widely distributed, based on review of earlier collections. Compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 35 publications
4
95
1
Order By: Relevance
“…5). Such a threshold value seems very high as critical oxygen levels for Nile perch are much lower (i.e., are between 2.5 and 3 mg l -1 ) (Kaufman & Ochumba, 1993;Wanink et al, 2001). For fish of 20-40 cm, densities were even negatively related with oxygen.…”
Section: Factors Determining Nile Perch Distributionsmentioning
confidence: 96%
“…5). Such a threshold value seems very high as critical oxygen levels for Nile perch are much lower (i.e., are between 2.5 and 3 mg l -1 ) (Kaufman & Ochumba, 1993;Wanink et al, 2001). For fish of 20-40 cm, densities were even negatively related with oxygen.…”
Section: Factors Determining Nile Perch Distributionsmentioning
confidence: 96%
“…Further, Kaufman and Ochumba (1993) using a remote operated vehicle in Lake Victoria found large numbers of dead or dying R. argentea below the oxycline. The authors suggested that rapid shifts in the oxycline may have caused the mass mortality.…”
Section: Fish Killsmentioning
confidence: 99%
“…Support for this 'hypoxic predation refugium' hypothesis came from exploratory dives by a remote operated vehicle, which filmed dagaa shoaling near the oxycline (Kaufman & Ochumba, 1993). Nile perch was in waters with a higher DO, but made short foraging grips into the hypoxic layer.…”
Section: Oxycline As Refugiamentioning
confidence: 99%
“…Of the three satellites, L. Kanyaboli is the largest (10.5 km 2 ) and most remote from L. Victoria [39], with a depth of 2.5-4.5 m [40]. Indigenous tilapias, O. esculentus, O. variabilis and O. leucostictus, which have been extirpated from L. Victoria, form the main fishery of L. Kanyaboli [31,36,41]. However, the invasion of the lake by exotic O. niloticus could threaten the survival of the indigenous tilapias, and negatively affect the fishery and livelihoods of the local community.…”
Section: Species Common and Local Names Distribution In Kenya Annotmentioning
confidence: 99%
“…Lake Victoria has a number of satellites: Kanyaboli, Namboyo and Sare, on the Kenyan side and Nabugabo on the Ugandan side. Satellite lakes have been recognized as important functional refugia for fish fauna, since they are connected to main lakes by extensive papyrus swamps that are anoxic to invasive predators like L. niloticus [29,31,[35][36][37]. Anoxic conditions prevent the natural entry of L. niloticus to these habitats, which are inhabited by indigenous fish fauna tolerant to low dissolved oxygen conditions, and this helps to conserve indigenous fish stocks (a valuable food resource for the local communities) from predation pressure, unless the invasive predator is introduced there by man.…”
Section: Satellite Lakesmentioning
confidence: 99%